Assessing environmental quality status by integrating chemical and biological effect data: The Cartagena coastal zone as a case. (March 2017) - Martínez-Gómez, Concepción; Fernández, Beatriz; Robinson, Craig D.; Campillo, J. Antonio; León, Víctor M.; Benedicto, José; Hylland, Ketil; Vethaak, A. Dick
Abstract: Cartagena coastal zone (W Mediterranean) was chosen for a practical case study to investigate the suitability of an integrated indicator framework for marine monitoring and assessment of chemicals and their effects, which was developed by ICES and OSPAR. Red mullet ( Mullus barbatus ) and the Mediterranean mussel ( Mytilus galloprovincialis ) were selected as target species. Concentrations of contaminants in sediment and biota, and contaminant-related biomarkers were analysed. To assess environmental quality in the Cartagena coastal zone with respect to chemical pollution, data were assessed using available assessment criteria, and then integrated for different environmental matrices. A qualitative scoring method was used to rank the overall assessments into selected categories and to evaluate the confidence level of the final integrated assessment. The ICES/OSPAR integrated assessment framework, originally designed for the North Atlantic, was found to be applicable for Mediterranean species and environmental matrices. Further development of assessment criteria of chemical and biological parameters in sediments and target species from the Mediterranean will, however, be required before this framework can be fully applied for determining Good Environmental Status (GES) of the Marine Strategy Framework Directive in these regions. Highlights: The ICES/OSPAR integrated framework was adapted for use in the western Mediterranean. The Cartagena coastal zone showed a "fair to good" environmental status. The main challenge to applying the approach is the paucity of Mediterranean assessment criteria. A method to quantify the confidence level of the final assessment has been proposed.